Analisis Proximate Briket Tempurung Kelapa dan Ampas Tebu - Setiani, Vivin; Setiawan, Adhi; Dhani, Mey Rohma; Maulidya, Risya Dwi (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2019)
Fossil fuels are a non-renewable energy source and their existence will be depleted. An alternative is needed that can reduce fossil fuels by using biomass. Biomass waste in the form of bagasse and coconut shell can be used as an alternative fuel in the form of biobriquette. This study aims to analyze the quality value of briquettes from the proximate test of the composition of bagasse and coconut shell produced with briquette quality standards that refer to SNI 01-6235-2000 about wood charcoal briquettes. The variables in this study consisted of five variables. The variables in this study were mass ratio coconut shells to bagasse were 90%: 10%, 80%: 20%, 70%; 30%, 60%: 40% and 50%: 50% respectively. The results of the test of water content, ash content, and volatile matter of the best quality briquettes of five variables were 90% coconut shell and 10% bagasse.